Analiza wydatków na reklamę w Polsce na tle wybranych państw europejskich w latach 1996-2000 - Skowronek-Grądziel, Agnieszka; Bartoszewicz, Bartłomiej (Analysis of advertising expenditures in chosen European countries 1996-2000, 2005)
In this paper advertising expenditures in chosen European countries are analysed. The authors claim that advertising expenditures in Poland are high with respect to the gross domestic product. This suggests that high increases in advertising expenditures should not be expected.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 117-127